Shame, Self-Criticism, Perfectionistic Self-Presentation and Depression in Eating Disorders - Costa, Joana (2016)
Costa, J., Marôco, J., Pinto-Gouveia, J., & Ferreira, C. (2016). Shame, Self-Criticism, Perfectionistic Self-Presentation and Depression in Eating Disorders. International Journal of Psychology and Psychological Therapy, 16(3), 317-328. http://www.ijpsy.com/volumen16/num3/449.html